Measurement challenges of supply chain performance in complex shipping environments - Panayides, Photis; Borch, Odd Jarl; Henk, Anastasiya (My University, 2018)
Purpose - Logistics service performance measurement (PM) is a fundamental activity pertaining to the achievement of logistics goals and the improvement of services. The choice of logistics PM criteria depends on stakeholder goals and expectations, including logistics service providers, customers and government and regulatory institutions. PM is especially challenging in areas where high values are at stake, several actors are involved and uncertainty about cause-and-effect relations is high. This paper aims to examine the measurement of performance in offshore oil and gas logistics, which has unique characteristics such as a supply chain (SC) exposed to a harsh environment, the presence of several independent carriers and a highly specialised and costly set of vessels involved in long-distance transport legs. Design/methodology/approach - The study is designed as a multiple case study of two Norwegian shipping companies and two international oil and gas companies. Data were collected from several parts of the offshore service SC in several Arctic oil and gas fields. Findings - This paper sheds light on the performance of the SC and presents key performance indicators for logistics operations. It concludes that the measurement of SC performance must be context-specific and emphasis needs to be placed on the degree of uncertainty and inter-dependency related to the SC in question. Originality/value - The study suggests a list of context-specific key performance indicators for offshore logistics with a special emphasis on the peculiarities of a harsh operational environment.
Keywords: Key performance indicators; Performance measurement; Offshore logistics